Analisis Bibliometrik Pada Pengembangan Media Pembelajaran Interaktif Matematika Berbasis Software Lectora Inspire - Septiani, Ira; Anggoro, Bambang Sri; Dewi, Novian Riskiana (Jurnal Ilmiah Global Education, 2024)
The development of technology in the 5.0 era, it is possible for students to use technology-based learning media. Such as interactive learning media that combines video, animation and audio so that it allows users to interact and understand the material. and increase learning that is more interesting and interactive. This research aims to determine the number of developments in research publications from 2017-2023 on Google Scholar, the level of researcher productivity, and a map of research developments. The method used is descriptive research with a quantitative approach using bibliometric analysis for publication mapping with the help of VOSviewer. Data collection techniques use the Publish or Perish application. The research results show that the development of publications in 2017-2023 with the highest G   oogle Scholar searches in 2023 was 57 publications with a percentage of 32.57%. The most productive authors in research are Supriadi, N., Sunaryo, S., Umbara, U., Yusuf, D., and Risdianto, E., with a total of 3 journal/article publications. The development map based on keywords produces 7 clusters. Meanwhile, the development map of research publications based on authors produces 156 clusters.